An improved method for examining meiotic chromosomes in Musa L. - Adeleke, M.; Pillay, M.; Okoli, B.E. (2002)
Meiotic studies in Musa L. have been hampered by: 1) time-consuming efforts required to find the correct stages of cell division; 2) rigidity of the microsporocyte cell wall that makes preparation of smears difficult; and 3) poor staining of prophase chromosomes. This study describes an improved technique to examine meiosis in Musa. The procedure involves dissection of microsporocytes from the anthers, centrifugation to obtain large number of microsporocytes, enzymatic digestion of cell walls and treatment of cells with acetic-alcohol that results in spontaneous bursting of the protoplasts and release of chromosomes. Previous meiotic studies in Musa used acetocarmine that stained only highly condensed metaphase and anaphase chromosomes easily but not the relaxed prophase stages. In this study, we found that silver nitrate, Giemsa and Leishmans’ stain were also effective for staining Musa chromosomes. Silver staining was most effective for the less contracted prophase chromosomes. By providing an improved procedure to examine all the meiotic stages in Musa, this technique will be useful to develop pachytenekaryotypes, characterize new hybrids and identify nuclear restitution mechanisms that are important in breeding schemes.